Identifying and Modeling the Interrelationships among Success Factors in MSME Mentoring Programs: An ISM–MICMAC Approach - Zaib Syahrul Mubaroq; Suhendi Suhendi; Zenal Asikin (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Micro, Small, and Medium Enterprises play a central role in Indonesia’s economy, yet many remain constrained by structural barriers that limit their growth beyond subsistence-level operations. In Garut Regency, despite the implementation of government-led mentoring initiatives such as the Wirahebat Program, business acceleration outcomes have remained uneven, indicating that assistance effectiveness depends on more than training delivery alone. This study aims to identify the key success factors of enterprise mentoring programs and analyze their structural relationships. A qualitative case study approach was employed involving government officials, mentors, academics, and program participants. The identified factors were analyzed using Interpretive Structural Modeling (ISM) and MICMAC analysis to determine their hierarchical and driving–dependence relationships. The findings reveal that enterprise mentoring effectiveness depends on an interconnected system rather than isolated interventions. Regional leadership, institutional coordination, and clear incubation design act as key driving forces, while participant selection, mentor relevance, coaching intensity, and post-program monitoring serve as critical linkage factors. Improved business competitiveness emerges as the main dependent outcome. This study highlights that sustainable mentoring requires alignment between policy, governance, program design, and participant readiness, offering a strategic framework for optimizing local enterprise development and strengthening inclusive small business ecosystems.